2006
DOI: 10.3171/jns.2006.104.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode-guided implantation of deep brain stimulators into the globus pallidus internus for dystonia: techniques, electrode locations, and outcomes

Abstract: Physiologically guided implantation of DBS electrodes in patients with dystonia was technically feasible in the awake state in most patients, and the morbidity rate was low. Spontaneous discharge rates of GPI neurons in dystonia were similar to those of globus pallidus externus neurons, such that the two nuclei must be distinguished by neuronal discharge patterns rather than rates. Active electrode locations associated with robust improvement (> 70% decrease in BFMDRS score) were located near the intercommissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
215
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(235 citation statements)
references
References 51 publications
(81 reference statements)
15
215
0
5
Order By: Relevance
“…57 Prior to recording, all patients were sedated with propofol for placement of the stereotactic frame as well as the surgical incision. Propofol is known to suppress basal ganglia discharge, 23 but is cleared rapidly, and prior studies in PD and dystonia suggest no neuronal effect of propofol following 30-60 minutes of washout time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Prior to recording, all patients were sedated with propofol for placement of the stereotactic frame as well as the surgical incision. Propofol is known to suppress basal ganglia discharge, 23 but is cleared rapidly, and prior studies in PD and dystonia suggest no neuronal effect of propofol following 30-60 minutes of washout time.…”
Section: Methodsmentioning
confidence: 99%
“…46 The MR images were computationally reformatted to be orthogonal to the anterior commissure-posterior commissure (AC-PC) line and midsagittal plane 57 (Framelink software, version 4.1, Medtronic), and lead tip locations were measured with respect to the midcommissural point ( Table 2, Fig. 1).…”
Section: Lead Locationsmentioning
confidence: 99%
“…38 Other groups have proposed that microelectrode recording provides important information for adequate lead placement in the GPi. 3,35 Starr et al have shown good lead placement in a mixed group of patients with different types of dystonia using microelectrode recording with few serious complications. 35 They have shown that even in patients who needed to be under general anesthesia they could achieve adequate mapping, but cautioned that propofol and inhalational agents should be avoided for optimal preservation of neuronal firing.…”
mentioning
confidence: 99%
“…3,35 Starr et al have shown good lead placement in a mixed group of patients with different types of dystonia using microelectrode recording with few serious complications. 35 They have shown that even in patients who needed to be under general anesthesia they could achieve adequate mapping, but cautioned that propofol and inhalational agents should be avoided for optimal preservation of neuronal firing. 35 Dexmedetomidine has been successfully used during DBS surgery in dystonic children, providing adequate sedation and analgesia without causing respiratory depression and allowing for patient cooperation during neurophysiological mapping.…”
mentioning
confidence: 99%
“…16 Anesthetics such as benzodiazepines, barbiturates, propofol, etomidate, and volatile agents potentiate the postsynaptic GABA effects by several actions that create an increased "open probability" for the GABA receptor channels. 17 Recent animal work on normal and MPTP-treated mice has shown abundant GABAergic innervations and GABA receptors in globus pallidus and that the endogenous GABA receptors modulate the spontaneous firing of globus pallidus neurons in normal mice. 3 Active spontaneous neuroelectrical firing from the globus pallidus is exceptionally sensitive to even small doses of anesthetic agents due to a large GABAergic input from the striatum.…”
Section: Discussionmentioning
confidence: 99%